Hybrids and allied species as potential rootstocks for eggplant: Effect of grafting on vigour, yield and overall fruit quality traits - Sabatino, Leo; Iapichino, Giovanni; D’Anna, Fabio; Palazzolo, Eristanna; Mennella, Giuseppe; Rotino, Giuseppe L. (Scientia horticulturae, 2018)
•Eggplant potential rootstocks including wild/allied species and hybrids were tested.•SPA and the hybrids Msa 2/2 E7 and 460 CAL. showed a good grafting success.•‘Birgah’ grafted onto SPA and Msa 2/2 E7 and 460 CAL. showed a good vigor and yield.•SPA, Msa 2/2 E7 and 460 CAL. did not induce negative effects on fruit quality traits.•Glycoalkaloids fruit concentration was always below the recommended safety value. Grafting of fruiting vegetables is an effective technique to overcome pests and diseases in modern cropping systems and it is often used to improve yield and fruit quality. Eggplant is an important vegetable crop that benefits significantly from grafting. In this regards, the exploitation, valorization and breeding of new rootstock genotypes as possible substitute to those commonly used (Solanum torvum and tomato hybrids) would permit an intensive eggplant crop system in those situations where a rootstock rotation is required. In the present article, we study the effects of several potential rootstocks including both wild/allied species of eggplant [S. torvum (STO), S. macrocarpon (SMA), S. aethiopicum (accession SASI), S. aethiopicum (accession SASa2), S. paniculatum (jurubeba) (SPA) and S. indicum (SIN)] and Msa 2/2 E7 and 460 CAL. eggplant hybrids on plant vigor, yield and fruit characteristics of eggplant F1 hybrid (‘Birgah’), in two spring-summer growing seasons (2014 and 2015). SPA and the hybrids Msa 2/2 E7 and 460 CAL. displayed a high percentage of grafting success. ‘Birgah’ scion grafted onto the two above-mentioned rootstocks showed a notable vigour and yield. Both rootstocks did not promote any unfavorable effects on apparent fruit quality traits and overall fruit composition. Furthermore, the concentration of glycoalkaloids in the fruit remained below the recommended safety value (200mg/100g of dw). These results suggest that SPA and Msa 2/2 E7 and 460 CAL. eggplant hybrids might represent a potential rootstock alternative to S. torvum.